Analysis of The Compatibility of Teaching Materials On The Ecology Topic Developed By The Teachers With Curriculum 2013 - Galih Nur Pratomo; Fida Rachmadiarti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
This research aimed to describe the compatibility of the teaching materials on the ecology topic developed by teacher with the Curriculum 2013. The teaching materials included lesson plan, teaching source, student worksheet, assessment and media learning. The sampels in this research were 3 schools in Surabaya that used Curriculum 2013. Researchers have developed research instruments and teaching material that have been validated by 2 validators, and the teaching materials were used to be as example to compare with the teacher’s teaching materials. Assessment of teaching material based on the completion component of lesson plan, compatibility of lesson plan content, compatibility of assessment with indicator, compatibility of instructional materials, compatibility of instructional media, and compatibility of student worksheet that have been developed. The data analysis was descriptive qualitative. Based on the data analysis, the percentage of teaching materials was 70.8%. It can be concluded that the teaching materials developed by the teacher was compatible with the Curriculum 2013.